Promote identification or prevent expansion? The effect of uploader-viewer similarity on viewer inspiration in the context of short video community - Fu, Senhui; Dai, Haiwen (Frontiers in Psychology, 2023)
In recent years, the number of short video communities has increased rapidly, which provides a new medium for the marketing of internet enterprises. How to inspire viewers' inspiration is the core issue of short video marketing. This study takes uploader-viewer similarity as the entry point and uses viewer social identification and self-expansion to explain the influence of similarity on short video inspiration. Based on the data of 310 short video viewers, the empirical analysis using SPSS26.0 and SmartPLS3.0 software found that there is a double-edged sword effect between uploader-viewer similarity and viewers' short video inspiration. Specifically, uploader-viewer similarity improves viewers’ perceived social identification while limiting their self-expansion. Viewers' cognitive needs moderate the relationship between uploader-viewer similarity and viewers' short video inspiration.